Surgical Site Infection: The Rate and Antimicrobial Sensitivity Pattern in Electively Operated Surgical and Gynecological Patients at Kilimanjaro Christian Medical Centre, Northern Tanzania - Ayesiga M. Herman; Gilead Massenga; Kondo S. Chilonga; Rune N Philemon; Denis Katundu; Anzbet Lugakingira; Joseph Obure (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Background: Surgical site infections are dreaded by many as they impose a greater economic costs, morbidity and mortality that in developing countries place a burden on an already burdened healthcare system. In Tanzania previously studies done in different centers reported high rates of Surgical Site Infection. This study aimed to quantify in a low income, tertiary hospital, the rate of Surgical Site infections, microorganisms implicated and their respective sensitivity pattern to local antibiotics, and associated perioperative risk factors in electively operated surgical and gynecological patients at Kilimanjaro Christian Medical Centre. Method: 301 patients admitted for elective procedures in the surgical and gynecological units were enrolled consecutively after consenting for the study. A standardized data collection form was used to record patients' information on perioperative risk factors. Patients were followed up in surgical outpatient clinic up to one month post discharge. Swabs from wounds showing signs of infection were taken for culture and sensitivity and processed at the laboratory as per standard operating procedures. Results: Out of a total of 301 patients, 181 patients were from general surgical ward and 115 from gynecological wards. Females were more than males (3:1) with most, 43.9% within the age group 40 to 60 years. Overall, 21.3% of the patients developed surgical site infection. 71 organisms were isolated, S. Aureus species were the leading cause of surgical site infections making 52% of the total isolates. Most of the gram positive organisms were resistant to ampicillin, the common antibiotic used in the gynecology unit. Contaminated wounds were 10 times more likely to develop surgical site infections, and clean contaminated wounds five times when compared to clean wounds. Duration of procedure, Surgeons skills, wound class and number of people in theater showed significant association with surgical site infection, however only wound class and duration of procedure remained statistically significant after a multivariate analysis. Conclusion: We found an SSI rate of 21.3%, slightly higher than previous studies in the same center. The wound class and duration of procedure remained significant risk factors after logistic regression analysis. As with other studies, S. Aureus was the most common causative organism for SSI isolated from our study.